ANALISIS PERANGKAT PEMBELAJARAN GEOGRAFI BERBASIS HIGH ORDER THINKING SKILL DI SMA NEGERI 7 KOTA PADANG - Charlos Decafrio; Nofrion Nofrion (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This study aims to analyze the development of high order thinking skill (HOTS) of geography learning tools that consists of: learning implementation plan (RPP), students’ worksheet (LKPD) and daily tests (UH). This research belongs to descriptive research by using quantitative approach and using document as objecks of study. The data of this research derived from learning implementation plan (RPP), students’ worksheet (LKPD) and daily tests (UH). The data were collected by using document analysis technique, percentage and descriptive technique. The results of this study indicate that development of High Order Thinking Skill (HOTS) in geography learning in terms of learning implementation plan (RPP) has reached 100% based on the indicators including learning methods, learning steps, and learning assessments. Furthermore, based on the students’ worksheet (LKPD), the developmentof High Order Thinking Skill (HOTS) has reached 100% which is indicated by the level of questions. Next, in terms of the learningoutcomes test in the form ofdaily tests (UH), the development of High Order Thinking Skill (HOTS) has only reached 56% which is indicated by the number of questions at the C4 (analyzing), C5(evaluating), C6 (Creating) levels. Therefore, it is hoped that the teacher will consider the distribution of cognitivelevels of questions so that the development of High Orderhinking Skill(HOTS) can be implemented in geography learning.